The reproducibility of physiological responses and performance profiles of youth soccer players in small-sided games - Hill-Haas, S.; Rowsell, G. J.; Coutts, A.; Dawson, B. (International Journal of Sports Physiology and Performance, 2008)
Small-sided games (SSGs) are frequently used as an alternative to interval training to provide an aerobic training stimulus.1 Although the variability of the physical, perceptual, and physiological responses during SSGs training has been previously established,2,3 an understanding of the reproducibility of the acute physiological responses and movement demands of these games, when completed within the same session and between different training sessions, is also important. This information may allow coaches to better control the SSG training process with soccer players. Consequently, the aim of this study was to determine the within- and between-training session reproducibility of two SSG formats (2 versus 2 and 4 versus 4 players) and two regimes (intermittent and continuous).